Information professionals' career confidential : straight talk and savvy tips - De Stricker, Ulla (Chandos information professional series., 2015)
Based in part on a selection of the author's past blog postings, Information Professionals' Career Confidential is a convenient, browsable, and illuminating pocket compendium of insights on topics relevant for information and knowledge professionals at any stage of their careers. This book collects comments on matters of interest to new and experienced information professionals alike in 1-2 minute "quick takes, inviting further thought. Topics range from the value of knowledge management and effective communication in organizations to assessing employers' perception of information profess.